2013
DOI: 10.1111/pce.12222
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of a p38‐like MAPK is involved in sensing cellular redox state and drives atypical tubulin polymer assembly in angiosperms

Abstract: Reactive oxygen species (ROS) imbalance is a stressful condition for plant cells accompanied by dramatic changes in tubulin cytoskeleton. Here, evidence is provided that alterations in ROS levels directly interfere with the phosphorylation state of a p38-like MAPK in the angiosperms Triticum turgidum and Arabidopsis thaliana. Both oxidative stress generators and chemicals inducing ROS scavenging or decreasing ROS production resulted in the accumulation of a phospho-p46 protein similar to p38-MAPK. Importantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Besides, phosphorylation of a p38-like MAPK was recently found involved in cellular redox sensing. It initiated signaling events leading to microtubule disruption (Livanos et al, 2014). Once again, investigations on the involvement and the mode of action of the cytoskeleton in response to O 3 should provide valuable information on this stress-specific signaling.…”
Section: The Cytoskeletonmentioning
confidence: 99%
“…Besides, phosphorylation of a p38-like MAPK was recently found involved in cellular redox sensing. It initiated signaling events leading to microtubule disruption (Livanos et al, 2014). Once again, investigations on the involvement and the mode of action of the cytoskeleton in response to O 3 should provide valuable information on this stress-specific signaling.…”
Section: The Cytoskeletonmentioning
confidence: 99%
“…18 Interestingly, these plants exhibit extremely elevated levels of a p46 p38-like MAPK. 35 It was recently found that in angiosperms the p46 MAPK is implicated in sensing cellular ROS level alterations. ROS overproduction as well as elimination of ROS levels resulted in the activation of this protein.…”
Section: Implications Of Cytoskeletal Contribution To Deliberate Ros mentioning
confidence: 99%
“…ROS overproduction as well as elimination of ROS levels resulted in the activation of this protein. 35 Once activated, p46 drives the assembly of atypical tubulin polymers. 35 This strengthens the view that the mechanisms maintaining homeostasis during low or elevated ROS levels are connected by feedback loops and tightly linked to cytoskeletal responses.…”
Section: Implications Of Cytoskeletal Contribution To Deliberate Ros mentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleus, designated as the cell's control centre, hosts genetic information and regulates gene expression. Crucial biological processes such as DNA repair, replication, transcription, and signalling are accomplished by nuclear proteins (NPs) in a concerted manner (Livanos, Galatis, Gaitanaki, & Apostolakos, ). Execution of such critical functions demands multilayered regulation.…”
Section: Introductionmentioning
confidence: 99%